German manufacturing withstands the rise of emerging economies - Martin Gornig; Alexander Schiersch (DIW Economic Bulletin, 2012)
Between 2000 and 2009, China became the second largest industrialized nation, while manufacturing industries in other emerging and many Eastern European countries also experienced very strong growth. However, Germany was largely able to maintain its share of global industrial output. In 2009, as in 2000, Germany's value added share represented around 6.5 percent. This shows that Germany as an industrial location had benefited from the 50-percent increase in global industry far more than the USA, Japan, and other Western European industrialized nations. The decisive factor here was that, despite the onset of the financial and economic crisis in 2008, German research-intensive industry was able to develop a leading position among the established economies. Sectors which particularly profited from this development include the manufacture of road vehicles, machinery, electrical machinery, and chemicals
Keywords: O10; O40; O57; 330; China; manufacturing industries; development of sector shares